Sensitivity of buffaloes (Bubalus bubalis) to heat stress. Issue 4 (2nd November 2019) - Choudhary, Bishwa Bhaskar; Sirohi, Smita
Abstract: Based on ten years of data (2001–10), consisting of 12 673 observations on fortnightly milk yield of buffaloes reared in a dairy farm located in the Northern sub-tropics (29°41′0″N, 76°59′0″E), the present study establishes the relationship between weather conditions and production performance of lactating buffaloes. The critical threshold level of maximum temperature-humidity index (THI) was estimated to be 74, which is higher than that of crossbred cows. The duration of discomfort period for buffaloes begins in mid-March and lasts up to early November. During the aggravated stress condition (THI > 82) prevailing in the region for about 5 months starting from early May, milk productivity declines by more than 1% per unit increase in maximum THI over 82. The maximum temperature and minimum humidity (viz. maximum THI) are the most critical weather parameters causing thermal stress in animals, however, the climatic conditions in the region are such that not only maximum but also minimum THI crosses the critical threshold providing little relief to the animals during the night.